Expression of lipoma preferred partner in mammary and extramammary Paget disease. Issue 51 (18th December 2020) - Liu, Ye; Wang, Yangbin; Qi, Ruiqun; Mao, Xiaoyun; Jin, Feng
Abstract: Backgound: This study aims to identify the expression of lipoma preferred partner (LPP) in Paget disease (PD) and to further understand the pathogenesis of PD. Methods: Tissue microarray was used to evaluate the expression of LPP by immunohistochemistry in 40 PD patients. The results of LPP expression were combined with clinical and histopathological characteristics. Patient files were analyzed retrospectively. Results: Twenty-one cases were mammary Paget disease (MPD) and 19 extramammary Paget disease (EMPD) involving the vulva, scrotum, and penis. LPP was expressed in PD and this expression was significantly greater in MPD versus EMPD ( P  = .031). The expression of LPP in MPD was significantly related with age ( P  = .009) and expression of Ki-67 ( P  = .011). No statistically significant differences were observed in LPP expression as related to sex, body location, and time of PD diagnosis. Conclusions: While LPP is expressed in both MPD and EMPD, the intensity of this expression is greater in MPD. LPP expression is positively correlated with Ki-67 and is more prevalent in middle-aged versus senior MPD patients. Further research is needed to determine its potential role in tumorigenesis and distribution.